Interior Gradient Estimates for General Prescribed Curvature Equations (Analysis in Theory and Applications, 2023)
In this paper, we derive the interior gradient estimate for solutions to general prescribed curvature equations. The proof is based on a fundamental observationof Gårding's cone and some delicate inequalities under a suitably chosen coordinate chart. As an application, we obtain a Liouville type theorem.